Social acculturation through short + sweet drama festival 2017: An analysis on selected plays / Muhammad Shukri Mohd Tahir - Muhammad Shukri , Mohd Tahir (2021)
This research focused on the three selected drama plays from the Short + Sweet Drama Festival 2017, a famous festival held yearly by the Actors Studio at the Kuala Lumpur Performing Arts Centre, Kuala Lumpur. Two objectives will be highlighted in this particular study. The first, to identify the essence of social acculturation elements embedded within the three selected scripts through organic solidarity. Secondly, to analyze the social acculturation impact through the experiences of the playwrights, directors and actors respectively, from the three selected theatre plays. This writing will be based on two different theories that connect two different sides of this particular research. One of these theories is Syd Fields’ (1979) three act structure or in other words ‘paradigm’, and also Emile Durkheim’s (1892) social solidarity theory. At the end of this writing journey, this research will be a solid proof in justifying that the performing arts platform (particularly theatre), can be the best channels to equipt the Malaysian society, with in-depth understanding and realization of the significance of social acculturation upon the growth, progress and harmony of our own unique nation.